Sutureless Microvascular Anastomosis using Intravascular Stenting and Cyanoacrylate Adhesive - Aizawa, Tetsushi; Kuwabara, Masahiro; Kubo, Satoshi; Domoto, Takashi; Aoki, Shimpo; Azuma, Ryuichi; Kiyosawa, Tomoharu (Journal of Reconstructive Microsurgery, 2018)
Background Microvascular anastomosis using cyanoacrylate adhesive has a reputation among researchers as an alternative to conventional sutures. However, a degree of ingenuity is required to avoid the collapse of the vascular lumen for the duration of the anastomosis. The aim of this study was to determine the feasibility of intravascular stenting (IVaS) as a temporary stent during sutureless microvascular anastomosis with cyanoacrylate adhesive.Methods Sixty male Fisher 344 rats were evenly divided into two groups. The right superficial femoral arteries (RSFAs) were transected in each group. Microvascular anastomoses were then performed with the sutureless (SL) method in one group and conventional sutures (CS) in the other group. The diameter of the RSFA, duration of microvascular anastomosis, and the patency of the RSFA were evaluated immediately after anastomosis and 7 days after the surgery. Tissue samples were obtained for pathological consideration.Results There was no significant difference in the diameter of the RSFAs between the SL and the CS groups. There was no significant difference in the patency rates of the groups. The anastomosis time of the SL group was significantly shorter than that of the CS group, regardless of the experience of the surgeons. A histological analysis showed a comparable level of foreign body reactions in each group.Conclusion IVaS plays a supportive role in sutureless microvascular anastomosis with cyanoacrylate adhesive. The short-term safety of this technique has now been confirmed at the experimental stage.
Keywords: intravascular stenting (IVaS); 2-octylcyanocrylate; surgical adhesive